Effects of dietary supplements on androgenetic alopecia: a systematic review and network meta-analysis - Zhou, Lei; Zhu, Wenkang; Chen, Yan (Frontiers in Nutrition, 2026)
BackgroundIn recent years, androgenetic alopecia (AGA) has emerged as a significant public health concern due to its high prevalence and progressive nature. In addition to progressive scalp thinning and hair loss, patients often experience psychological distress and diminished quality of life. While standard treatments such as finasteride and minoxidil are effective, their side effects and adherence issues limit long-term use, making the exploration of safe and accessible intervention strategies essential. Dietary supplements, claimed to promote hair growth by inhibiting androgen pathways and improving the follicular microenvironment, have become an attractive adjunct for both clinicians and patients due to their low cost and ease of use. However, existing studies have limitations, including the diversity of supplements, small sample sizes, and the lack of direct comparisons among different supplements, making it unclear how they compare in terms of efficacy and safety. This study aims to use a network meta-analysis (NMA) to compare the effectiveness and safety of various dietary supplements based on outcomes such as hair density and terminal hair density, providing evidence-based support for clinical decision-making.MethodsA systematic search was conducted in English-language databases such as PubMed, Cochrane Library, Embase, and Web of Science for randomized controlled trials (RCTs) investigating the use of dietary supplements for treating AGA. Stata 16.0 software was used for network meta-analysis, and Revman 5.4 software was utilized for evaluating study quality and bias risk; additionally, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework was applied to rate the certainty (quality) of evidence for the included studies.ResultsA total of 19 RCTs involving 1,658 AGA patients were included, with 894 patients in the supplement group and 764 in the control group. Sixteen dietary supplements were investigated. Results showed that compared with placebo, standardized plant extracts (Nutrafol), apple extract (AMSbzs, AMS), tocotrienols, pumpkin seed oil (PSO), and a compound extract of Cistanche and Laminaria (MK-R7) significantly improved hair density. Multi-component supplements (ALRV5XR), standardized plant extracts (Nutrafol), and probiotics effectively increased terminal hair density. In blind doctor assessments, PSO, capsaicin-isoflavones (CI), saw palmetto extract (ESR), Omega 3&6, Lambdapil, Nutrafol, and Multi-component supplements (AGA-P) showed higher hair regeneration scores than placebo or conventional treatments. No significant differences were found between interventions in terms of the terminal-to-vellus hair ratio. Overall, all dietary supplements were found to be well-tolerated.ConclusionDietary supplements have a positive impact on hair density, terminal hair density, and blind doctor evaluations in patients with androgenetic alopecia, with good tolerability. They may serve as beneficial adjuncts or alternatives to conventional treatments. Future large-scale, high-quality RCTs are needed to verify these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251130173, Identifier CRD420251130173.